2021
DOI: 10.1038/s41598-021-91410-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological factors predicting outcomes of nonfermenting gram-negative bacilli peritonitis in peritoneal dialysis

Abstract: Peritonitis due to gram-negative bacilli (GNB), particularly nonfermenting GNB (NF-GNB), is a serious complication of peritoneal dialysis with a low resolution rate. Beyond the patient’s condition, microbiological properties such as antimicrobial resistance, biofilm production and other virulence factors can explain the poor outcomes. This study aimed to evaluate the influence of patient condition, microbiological characteristics, including biofilm production, and treatment on peritonitis outcome. We reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 38 publications
1
7
0
5
Order By: Relevance
“…As previously published by our group [19], the results of the present study confirmed the predominance of P. aeruginosa species as etiologic agents of BGNNF peritonitis [10] in patients treated for PD. Pseudomonas peritonitis is usually severe and is often associated with catheter infection.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…As previously published by our group [19], the results of the present study confirmed the predominance of P. aeruginosa species as etiologic agents of BGNNF peritonitis [10] in patients treated for PD. Pseudomonas peritonitis is usually severe and is often associated with catheter infection.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study by our group was not able to identify which clinical factors, treatments employed, or microbiological factors of the NF-GNB causing peritonitis on peritoneal dialysis were related to the outcomes of this infection; only exit-site infection (ESI) was identified as an independent predictor of non-resolution of these infections [19]. Then, the pathogenic profile of NF-GNB may explain, at least partially, the bad outcomes of PD-related peritonitis.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations